Personality, loneliness and mental health among undergraduates at Malaysian Universities - Md Nordin, Noradilah; Abu Talib, Mansor; Yaacob, Siti Nor (EuroJournals Publishing, 2009)
The aim of this study was to examine the relationship between personality and loneliness on mental health among undergraduates at Malaysian Universities. A total of 1468 respondents were recruited from five Universities using the multistage cluster sampling. Mental health was measured by 12 items in the General Health Questionnaire (GHQ-12) designed by Goldberg, 1978. Personality and loneliness were measured using the Big Five Inventory (John, Donahue and Kentle, 1991) and the revised UCLA Loneliness Scale (Russell, Peplau and Cutrona, 1980) respectively. A cut-off point of 5/6 for the GHQ-12 was used in this study. The results of this study revealed that a total of 65.6% of Malaysian undergraduates exhibited healthy mental health and 34.4% showed indications of mental health problems. Apart from that, this study also found a significant relationship between extraversion, agreeableness, conscientiousness, neuroticism, openness and loneliness on mental health. Analysis of one-way ANOVA found a significant difference in mental health between year of study, field of study, ethnicity and religion. Finally, the multiple regression analysis using the stepwise method yielded R2 of 0.103 which means that only 10.3% of variation in the mental health was explained by the predictors. Loneliness was the most significant predictor in explaining mental health followed by neuroticism and extraversion personality. Early detection for indications of mental health problems and understanding factors contributing to stress among students would promote better understanding of mental health in future.